DOCK6 Mutations Are Responsible for a Distinct Autosomal‐Recessive Variant of Adams–Oliver Syndrome Associated with Brain and Eye Anomalies. Issue 6 (21st April 2015) - Sukalo, Maja; Tilsen, Felix; Kayserili, Hülya; Müller, Dietmar; Tüysüz, Beyhan; Ruddy, Deborah M.; Wakeling, Emma; Ørstavik, Karen Helene; Snape, Katie M.; Trembath, Richard; De Smedt, Maryse; van der Aa, Nathalie; et al.
<x xml:space="preserve">Abstract</x> This article reviews 17 DOCK6 mutations including 11 novel ones observed in 15 families affected by Adams‐Oliver syndrome. Homozygous or compound‐heterozygous DOCK6 mutations were strongly associated with structural brain abnormalities, ocular anomalies, and intellectual disability, thus suggesting that DOCK6‐linked disease represents a variant of AOS with a particularly poor prognosis.